2004
DOI: 10.1364/josaa.21.001455
|View full text |Cite
|
Sign up to set email alerts
|

General adaptive-neighborhood technique for improving synthetic aperture radar interferometric coherence estimation

Abstract: A new method for filtering the coherence map issued from synthetic aperture radar (SAR) interferometric data is presented. For each pixel of the interferogram, an adaptive neighborhood is determined by a region-growing technique driven by the information provided by the amplitude images. Then pixels in the derived adaptive neighborhood are complex averaged to yield the filtered value of the coherence, after a phase-compensation step is performed. An extension of the algorithm is proposed for polarimetric inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…For this reason interferometric amplitudes are used to specify filter weights, which are finally determined by utilizing a MonteCarlo scheme. Approaches on adaptive complex Multilooking motivated by coherence filtering are published by Ciuc et al 2002 andVasile et al 2004. Both start with a statistical analysis of SAR amplitude data, followed by a twostage region growing on the same data.…”
Section: Related Workmentioning
confidence: 99%
“…For this reason interferometric amplitudes are used to specify filter weights, which are finally determined by utilizing a MonteCarlo scheme. Approaches on adaptive complex Multilooking motivated by coherence filtering are published by Ciuc et al 2002 andVasile et al 2004. Both start with a statistical analysis of SAR amplitude data, followed by a twostage region growing on the same data.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, adaptive algorithms making use of amplitude statistics to fuse pixels with the same features are here analyzed. The algorithm in (Vasile et al, 2004), connecting pixels with a region growing technique, and the one in (Deledalle et al, 2011), connecting also not consecutive pixels inside a search window, are tested. The need to employ adaptive methods is clear looking at Fig.…”
Section: Interferogram Generation Stagementioning
confidence: 99%
“…An example of Raw DEM over Berlin, processed with the region growing algorithm (Vasile et al, 2004), with a theoretical resolution of 2 meters, is shown in Fig. 12.…”
Section: Interferogram Generation Stagementioning
confidence: 99%
“…The proposed procedure consists in gathering only the pixels which belong to the same HR spatial feature and respect the "local stationarity" hypothesis [6]. Under the assumption that small homogeneous regions within the two intensity images correspond to ground areas with an homogeneous cover which should respect the stationarity hypothesis, the multi-resolution technique employed in this paper is the Amplitude-Driven-AdaptiveNeighborhood (ADAN) [3].…”
Section: B Spatial Supportmentioning
confidence: 99%
“…The next generation of SAR satellites should provide meter resolution images and fully polarimetric data, which will be very useful to detect different features and backscattering mechanisms and to improve the extraction of the geometric deterministic component of the interferometric phase by adaptive techniques [3]. The two main limitations of the glacier InSAR measurements are the temporal decorrelation and the need to separate the topographical fringes from the displacement fringes.…”
Section: Introductionmentioning
confidence: 99%